2007
DOI: 10.1016/j.jcomdis.2006.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety levels in adolescents who stutter

Abstract: High levels of anxiety can negatively affect the lives of children and adolescents. Thirty-six adolescents who stutter and 36 adolescents who do not stutter were administered standardized scales for anxiety and self-esteem. Significant differences were found for the total T-scores for Revised Children's Manifest Anxiety Scale for the two groups, although both groups mean T-scores were within normal range. Eighty-three percent of adolescents who stutter and 95% of adolescents who do not stutter earned scores in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(44 citation statements)
references
References 71 publications
(72 reference statements)
4
39
0
1
Order By: Relevance
“…The finding that adolescents who stuttered displayed significantly higher trait, state and social anxiety than did control participants is consistent with results obtained by Blood et al (2007), whereby significant differences were reported on a generalised anxiety scale between adolescent participants who did and did not stutter. This suggests that adolescents who stutter are at risk of developing higher levels of anxiety than their fluent peers.…”
Section: Anxiety In Adolescents Who Stuttersupporting
confidence: 89%
See 4 more Smart Citations
“…The finding that adolescents who stuttered displayed significantly higher trait, state and social anxiety than did control participants is consistent with results obtained by Blood et al (2007), whereby significant differences were reported on a generalised anxiety scale between adolescent participants who did and did not stutter. This suggests that adolescents who stutter are at risk of developing higher levels of anxiety than their fluent peers.…”
Section: Anxiety In Adolescents Who Stuttersupporting
confidence: 89%
“…It is possible that rather than playing a mediating role in stuttering, increased anxiety among adolescents who stutter is, in fact, a by-product of the stuttering disorder regardless of its surface manifestation. Blood et al (2007) also found no significant correlation between a standard anxiety measure and stuttering severity. The present study therefore supports their findings and suggests that an association is not observed even when stuttering typography is taken into account.…”
Section: The Role Of Social Anxiety In Severity and Typographymentioning
confidence: 70%
See 3 more Smart Citations